"Down Woodward": A Case Study of Empowering Youth to See and Disrupt Segregation Using Photovoice Methods. Issue 1 (January 2021) - Aldana, Adriana; Richards-Schuster, Katie; Checkoway, Barry
This case study examined how the Michigan Youth Policy Fellows program—which aimed to create a space for a team of adolescents to engage in a collaborative photovoice project with peers from diverse backgrounds—empowered young people to critically analyze and interrupt racial segregation. The study describes how nine racially and socioeconomically diverse adolescent girls and boys (14–17 years old), from the inner city and suburbs of Detroit, collectively evaluated the cultural, economic, and racial markers of differences found along one of the region's thoroughfares, Woodward Avenue. The case study used multiple sources of data, collected over 8 years from 2006 to 2014, and a hybrid inductive-deductive analysis approach to examine the process of youth empowerment. The collaborative nature of the photovoice tour helped youth move from critical self-reflection of lived experiences to a collective understanding of segregation and inequality in the metropolitan region. The findings also suggest that engagement in a photovoice project fostered collective action through intergroup advocacy and supported youths' civic development. As a practical method, the case study demonstrates that photovoice is a useful tool for group empowerment with adolescents.